Farm data management, sharing and services for agriculture development online course - Technical Centre for Agricultural and Rural Cooperation; Pan-African Farmers' Organization; Food and Agriculture Organization of the United Nations (CTA, PAFO and FAO, 2020)
The online course "“Farm Data Management, Sharing and Services for Agriculture Development” was delivered two times from October to December in 2019. It accommodated over 5,000 participants from 153 different countries. It was aimed to strengthen the skills of professionals who use, manage data for the benefit of farmers and farmers organisations by exposing them to the topics of importance of data in the agriculture value chain and how new and existing technologies, products and services can leverage farm level and global data to improve yield, reduce loss, add value and increase profitability and resilience.